PERANCANGAN GEDUNG OLAHRAGA TIPE B DI KABUPATEN KUBU RAYA - Agan, Felisianus Diogenes; Khaliesh, Hamdil; BR Gultom, Bontor Jumaylinda (JMARS: Jurnal Mosaik Arsitektur, 2024)
Sports from time to time are increasingly in demand by the general public and students who want to find fitness and physical health. Currently, Kubu Raya Regency does not have an adequate sports facility container, so it is not optimal in carrying out activities that can improve the quality and quality of athletes. The design is located on Jl. Soekarno Hatta, Sungai Raya District, Kubu Raya Regency, West Kalimantan Province. The purpose of design, supporting indoor sports activities in it ranging from sports, competition, recreation, and versatile activities. The design used, through the stages of primary and secondary data collection, analysis, synthesis, and pre-design results. The main function of design as a place for competition and training activities, the secondary function as a service function managed by the manager of the Sports Hall, and the supporting function as a general recreational and multipurpose activity. Based on the classification of Sports Buildings in the Regency / City area, Type B can accommodate around 1000-3000 people, including badminton, volleyball, basketball, futsal, field tennis, sepak takraw, and martial sports. The design theme, applying the principle of wide-span building character, by expressing roof structural elements, the use of renewable materials (glass, steel, and aluminum), and dynamic building shapes in the entire building, as well as lifting the philosophy of Kubu Raya Regency uphill which can be seen in the formation of the roof of the building in displaying attractive faÃ§ade display elements in giving birth to the spirit of sports.